2012
DOI: 10.1073/pnas.1211198109
|View full text |Cite|
|
Sign up to set email alerts
|

Heptahelical protein PQLC2 is a lysosomal cationic amino acid exporter underlying the action of cysteamine in cystinosis therapy

Abstract: Cystinosin, the lysosomal cystine exporter defective in cystinosis, is the founding member of a family of heptahelical membrane proteins related to bacteriorhodopsin and characterized by a duplicated motif termed the PQ loop. PQ-loop proteins are more frequent in eukaryotes than in prokaryotes; except for cystinosin, their molecular function remains elusive. In this study, we report that three yeast PQ-loop proteins of unknown function, Ypq1, Ypq2, and Ypq3, localize to the vacuolar membrane and are involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
184
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(205 citation statements)
references
References 73 publications
4
184
2
4
Order By: Relevance
“…Evidence for the involvement of this transporter in the cysteamine-driven depletion of cystine was obtained by its genetic inactivation or silencing [19,20]. Molecular modeling has shown the structural and electronic similarities of the L-cysteine-cysteamine mixed disulfide to L-lysine, facilitating its use of this transporter [21].…”
mentioning
confidence: 99%
“…Evidence for the involvement of this transporter in the cysteamine-driven depletion of cystine was obtained by its genetic inactivation or silencing [19,20]. Molecular modeling has shown the structural and electronic similarities of the L-cysteine-cysteamine mixed disulfide to L-lysine, facilitating its use of this transporter [21].…”
mentioning
confidence: 99%
“…Atg22 mediates the efflux of leucine and other amino acids resulting from autophagic degradation, and also redundantly functions with Avt3 and Avt4 (Yang et al, 2006). In the homeostasis of cationic amino acids, the vacuolar basic amino acid transporter (VBA)-family member proteins Vba1, Vba2, and Vba3 (Shimazu et al, 2005) and the PQ-loop proteins Ypq1, Ypq2, and Ypq3 (Jézégou et al, 2012) are specifically involved in the import and export of basic amino acids, respectively. Since proline is one of the nonpreferred nitrogen sources, the analysis of intracellular localization of proline has been difficult under typical nutrient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Jézégou et al 5) described in the previous paper that Ypq1p as well as Ypq2p is involved in export of basic amino acids from vacuoles, because ypq1Δ mutant acquired resistance to canavanine although it was weaker than ypq2Δ mutant. Accumulation of the drug into vacuoles might be accelerated in ypq1Δ mutant, resulting in decrease of its cytosolic level.…”
mentioning
confidence: 99%
“…1(A)) although these functions were not investigated. Very recently, Jézégou et al 5) reported a new closest homolog YPQ2 (YDR352W) in S. cerevisiae ( Fig. 1(A)).…”
mentioning
confidence: 99%
See 1 more Smart Citation